2015
DOI: 10.1021/acs.jpcb.5b02122
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Permeation of a Peptide: It Is Better to be Positive

Abstract: A joint experimental and computational study investigates the translocation of a tryptophan molecule through a phospholipid membrane. Time dependent spectroscopy of the tryptophan side chain determines the rate of permeation into 150 nm phospholipid vesicles. Atomically detailed simulations are conducted to calculate the free energy profiles and the permeation coefficient. Different charging conditions of the peptide (positive, negative, or zwitterion) are considered. Both experiment and simulation reproduce t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(69 citation statements)
references
References 49 publications
3
66
0
Order By: Relevance
“…These types of approximations are very useful as the system grows in complexity and size and exact calculations become prohibitively expensive. Milestoning made it possible to investigate kinetics of enzymes [37] and transport through membranes [12] in agreement with experimental observations. These are systems of tens to hundreds of thousands of particles and time scales of milliseconds.…”
Section: Discussionsupporting
confidence: 52%
“…These types of approximations are very useful as the system grows in complexity and size and exact calculations become prohibitively expensive. Milestoning made it possible to investigate kinetics of enzymes [37] and transport through membranes [12] in agreement with experimental observations. These are systems of tens to hundreds of thousands of particles and time scales of milliseconds.…”
Section: Discussionsupporting
confidence: 52%
“…25 Previous studies of tryptophan using the more advanced method of milestoning report permeation times on the time scale of hours, which are also in agreement with experimental results. 43,44,85,86 Most other studies have also reported much larger and faster permeability coefficients using the inhomogeneous solubilitydiffusion model, which has been discussed in great detail in other works. 18,25,43,44,[87][88][89] Several assumptions underpin the solubility-diffusion model, including memoryless, diffusivetype motion along the reaction coordinate and the presence of only one slow variable describing the motion of the permeant-namely, the translocation along the membrane normal.…”
Section: Permeability Measuresmentioning
confidence: 79%
“…15,89 Many recent studies suggest that an additional rotational barrier exists that slows down the movement of the permeant. 18,43,44,87,89,90 Others hypothesize that membrane and solvent structural fluctuations play an important role as well. 39,85 The CHARMM lipid force field also overestimates the electric field strength within the membrane by a factor of 3, which may be lowering the value of the PMF within the membrane interior and subsequently accelerating the mean passage time.…”
Section: Permeability Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Distribution of 17 amino-acid analogs (without main-chain backbone atoms) across a dioleoylphosphatidylcholine (DOPC) bilayer [ 17 ] was obtained by umbrella sampling and revealed the importance of water defects in permeation of polar and charged residues. Other studies focused on the permeation mechanism of specific charged residues such as charged tryptophan [ 18 ] and arginine [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%